Correlation between Glasgow prognostic score and tumor-node-metastasis staging in colorectal cancer - Yazdani, Asif; Masum, Nazmul Hoque; Parveen, Rumana; Sazzad Hossain, M.; Hafizur Rahman Dipu, M. (International Surgery Journal, 2025)
Background: Colorectal cancer (CRC) prognosis is closely linked to clinical stage, with early-stage CRC offering better survival. This study aims to evaluate the relationship between the Glasgow prognostic score (GPS) and tumor-node-metastasis (TNM) staging in CRC. The aim of the study was to evaluate the relationship between the GPS and TNM staging in colorectal cancer Methods: This cross-sectional study, conducted from June 2018 to May 2019 in the Department of Surgery at Dhaka Medical College Hospital (DMCH), Dhaka, Bangladesh, included 100 colorectal cancer patients. It assessed the correlation between GPS and TNM staging. Data on demographics, tumor site, GPS, and TNM stage were analyzed using Chi-square tests in statistical package for the social sciences (SPSS) version 22.0, with significance set at p<0.05. Results: The study included 100 participants, predominantly male (59%), with a mean age of 65±10 years. The most common tumor sites were the left colon (42%) and rectum (29%). Elevated CRP levels (>10 mg/l) were observed in 25% of participants, and 34% had low albumin levels (≤35 g/l). Most participants had a GPS of 0 (56%), with 29% and 15% having GPS 1 and 2, respectively. Half of the participants were classified as TNM stage III, and 26% as stage IV. Higher GPS values significantly correlated with advanced TNM stages (p=0.0123). Conclusions: The study demonstrated a significant relationship between the GPS and TNM staging in colorectal cancer, highlighting GPS as a potential tool for assessing disease progression.